Esophageal atresia and Tracheoesophageal fistula with associated anomalies in a tertiary care hospital of north India - Prasad, Jagdeesh (International Surgery Journal, 2017)
Background: Esophageal atresia (EA) with or without Tracheoesophageal fistula (TEF) has been described as the epitome of pediatric surgery and the management of these neonates require high degree of skill, manpower and tertiary care. This clinical study was undertaken to identify the EA and TEF cases along with the pattern of associated anomalies causing mortality in Varanasi . Methods: This prospective study included 53 patients of EA with TEF who underwent primary esophageal anastomosis. Their clinical profile, time of presentation, various associated anomalies, sex distribution, and their effect on mortality and morbidity were observed. Results: Mortality was high (41.64%) among patients who reached the tertiary centre late i.e. >24 hours. The incidence of low birth weight babies is approximately 75% and mortality rate increased with low birth weight. Almost 2/3 of patients had clinical or radiological evidence of pneumonia. The mortality was very high in severe pneumonia 66.7% as compared to 15% patients without pneumonia. Septicaemia and leak were most common complications. The mortality in septicemic patients is high (77.8%). The overall incidence of associated anomalies was 47%. Early surgical intervention improved the survival of EA with TEF with major GIT associated anomalies. The overall survival rate was 60.37% and mortality was 39.67%. Conclusions: Although we have improved a lot in managing these cases of EA with TEF, but we have to do much more to achieve our goal of near 100% survival.